Dissecting Real Exchange Rate Fluctuations in China. Issue 2 (26th January 2018) - Chen, Yong; Liu, Dingming
ABSTRACT: This article uses a structural VAR model to investigate the sources of real exchange rate fluctuations in China over the period 1995Q1–2015Q4, taking into account five different types of macroeconomic shocks including technology, government spending, monetary policy, foreign demand, and risk premium shocks. These shocks are identified using sign restrictions derived from predictions of an open economy general equilibrium model calibrated to China's economy. We find that foreign demand shocks are the most important driving force of China's real exchange rate, which explains approximately 20% to 40% of the variance in 20 quarters. It is in line with the findings in the literature which show real demand shocks are the key contributor to fluctuations in the real exchange rate. Nominal shocks such as monetary policy shocks and risk premium shocks play relatively important roles at the short-term horizons, but their effects decay rapidly.